Sensitivity of an idealized subtropical gyre to the eastern boundary conditions - Láiz, Irene; Sangrá Inciarte, Pablo; Pelegrí Llopart,José Luis; Marrero Díaz, María de los Angeles (2001)
The flow pattern of the North Atlantic Subtropical Gyre (NASG) is simulated using a highly idealised one-layer quasi-geostrophic wind-driven model. The novel feature of the model is the specification of the eastern boundary conditions. This is an upwelling favourable region with a quasi-permanent southward flowing coastal jet, which is fed by the eastern branch of the Canary Current. The corresponding boundary conditions are non-zero normal flux and constant potential vorticity, the latter being consistent with the generation of anticyclonic vorticity by the coastal jet. We examine the sensitivity of the model to the eastern boundary conditions and compare the results with recent observations for the region.